Evaluation the efficiency of packing frozen vegetables that available in Iraq markets (Journal of the College of Basic Education, 2022)
The efficiency of packaging 15 samples of some types of frozen vegetables available in the local market of Baghdad were determined by labeling information and leakage, the results showed that the samples V5, V6 and V10 were conforming to the requirements of the Iraqi standard No. 1847 of 2012 (the second update / shelf life of foodstuffs) and its amendments by mentioning the month and year, while the samples V1, V2, V3, V4, V7, V8, V9, V11, V12, V13, V14 and V15 did not conform the specification requirements by mentioning the day, month and year, it was noted that the samples V3, V4, V11 and V15 did not mention the producing company or the importer, the results indicated that the samples V11 and V15 did not mention the batch number, while all samples were content name of material, trademark, country of origin, storage conditions, warning mark, weight and language of the label. The results of the leak test for the frozen vegetable samples showed the presence of leakage in the samples V2, V8, V10, V11 and V14. Keywords: Frozen vegetables, packaging efficiency, informational label, leakage